Species and Phenotypic Distribution Models Reveal Population Differentiation in Ethiopian Indigenous Chickens - Kebede, Fasil Getachew; Komen, Hans; Dessie, Tadelle; Alemu, Setegn Worku; Hanotte, Olivier; Bastiaansen, John W. M. (Frontiers in Genetics, 2021)
Smallholder poultry production dominated by indigenous chickens is an important source of livelihoods for most rural households in Ethiopia. The long history of domestication and the presence of diverse agro-ecologies in Ethiopia create unique opportunities to study the effect of environmental selective pressures. Species distribution models (SDMs) and Phenotypic distribution models (PDMs) can be applied to investigate the effect of environmental factors on local adaptation in wild animals and domestic populations. In the present study we used SDMs and PDMs to detect environmental variables related with habitat suitability and phenotypic differentiation in domestic chicken populations in Ethiopia. Thirty-four environmental (climatic, soil, vegetation) and 19 quantitative phenotypic variables were analyzed for 513 adult birds from 26 populations. To have high variation in the dataset for phenotypic and ecological parameters, animals were sampled from four spatial gradients (each represented by 6-7 populations), located in different climatic zones and geographies. Three different ecotypes are proposed based on correlation test between habitat suitability maps and phenotypic clustering of sample populations These specific ecotypes show phenotypic differentiation, likely in response to environmental selective pressures. Nine environmental variables with the highest contribution to habitat suitability are identified. The relationship between phenotypic variables and a few of the environmental variables associated with habitat suitability is non-linear. Our results highlight the benefits of integrating species and phenotypic distribution modelling approaches in characterization of livestock populations, delineation of suitable habitats for specific breeds, and understanding of the relationship between ecological variables and phenotypic traits.